Towards effective monitoring of sand mining sites and post management techniques in sand dredged environment of Akwa Ibom State, Nigeria - Abraham CM; Essien K; Umoh EU; Umoh EC; Ehiremem LE; Akpan V; William NI (Global Journal of Ecology - Peertechz Publications, 2021)
The study examined Sand Dredged Environment of Akwa Ibom State, Nigeria towards effective monitoring of sand mining mites and post-management techniques. Multi-stage random sampling was used to select nine (9) Local Government Areas and three (3) communities from the selected local Government Areas in Akwa Ibom State. Primary data were collected with structured questionnaires and focus group discussion. The study reveals that post-management guidelines of sand mining environment was not adopted in the study area to the failure in management of the environment in which a larger expanse of agricultural land have been converted to waste land and borrow pit. This work found that acquisition of sand mining permit was grossly ignored among sand miners in some mining communities, whereas other miners who obtained their permit deliberately hired too many dredgers in their allocated sand mining sites and the stakeholders mandated to monitor sand mining sites did not visit the sites and were relatively unaware of the illegal businesses going on in the sand mining sites. Chi-square was used to examine the impact of stakeholders on management of sand mining environment. The result indicated that a value of 204.565 at p<0.05 was obtained and it was concluded that stakeholders in the solid mineral exploration industry should re-direct their interest toward post-management of sand mining environment so as to restore degraded ecosystem for further land use purposes.